2011
DOI: 10.1089/end.2010.0606
|View full text |Cite
|
Sign up to set email alerts
|

Operating Times and Bleeding Complications in Percutaneous Nephrolithotomy: A Comparison of Tract Dilation Methods in 5537 Patients in the Clinical Research Office of the Endourological Society Percutaneous Nephrolithotomy Global Study

Abstract: This study shows that in PCNL, factors that are associated with bleeding/transfusion include sheath size, operating time, stone load, and caseload.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
126
2
9

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 213 publications
(144 citation statements)
references
References 23 publications
7
126
2
9
Order By: Relevance
“…The predictive factors of bleeding in PNL were operating time, stone load, caseload, and sheath size (19)(20)(21). In our study, multivariate analysis showed that the only predictive factor of bleeding was operation time (P = 0.001; Figure 2; Table 3).…”
Section: Discussionmentioning
confidence: 47%
See 1 more Smart Citation
“…The predictive factors of bleeding in PNL were operating time, stone load, caseload, and sheath size (19)(20)(21). In our study, multivariate analysis showed that the only predictive factor of bleeding was operation time (P = 0.001; Figure 2; Table 3).…”
Section: Discussionmentioning
confidence: 47%
“…In the CROES study, patients whose operations lasted longer than 75 min (76-115 min) had statistically significantly more severe postoperative complications compared with those whose operative time was shorter than 50 min. The risk of more severe postoperative complications increased even further for those whose operative time was more than 115 min (20). In another study, Akman et al found a cut-off point for blood transfusion as 58 min.…”
Section: Discussionmentioning
confidence: 99%
“…Las principales complicaciones menores observadas en la NLP son la necesidad de transfusión (11.2-17.5%), la fiebre (21-32%) y el urinoma (0-1%); y las complicaciones mayores pueden ser lesión cólica (0.2-0.8%) o pulmonar (0.0-3.1%), sepsis (0.3-4.7%) y muerte (0.0-0.3%). A pesar de que la comorbilidad del paciente aumenta el riesgo de complicaciones, la mayoría de estas se resuelven de manera conservadora o por procedimientos mínimamente invasivos, presentando una evolución posquirúrgica normal en el 76.7% de los casos 1,[5][6][7] . Dentro de los tipos de abordajes para la NLP, el tradicional consiste en la dilatación progresiva del trayecto creado para colocar la camisa de acceso y de trabajo.…”
Section: Introductionunclassified
“…Pese a la seguridad de este procedimiento, se ha observado un mayor tiempo de exposición a rayos X (fluoroscopía) tanto del paciente como del personal de salud, así como mayores pérdidas hemáticas. El abordaje realizado en un paso pareciera ser más traumático para alcanzar las dimensiones necesarias para colocar la camisa de acceso en un solo acto, pero se ha observado que reduce el tiempo de exposición a la fluoroscopía y la tasa de complicaciones 7 . El objetivo del estudio fue determinar si existe beneficio del procedimiento en un paso en pacientes con litiasis renal en nuestro centro hospitalario.…”
Section: Introductionunclassified
“…Traditionally, PCNL has been performed in the prone position 2 , due to surgeon's familiarity, posterior calyceal puncture, larger surface area for puncture, avoidance of bowel injuries.However, the prone position has anaesthetic disadvantages 3 , especially in overweight and obese patients, or those with pulmonary complications. The modified supine position (The Galdakao-modified Valdivia position) offers several advantages 4,5,6 , reduced impact on the patient's circulatory and ventilatory system, easier monitoring of anaesthesia, simultaneous retrograde access, patient needs to be draped only once and no need of patient reposition. The main characteristic is a slight lateralisation of the Valdivia supine position, with the contralateral leg flexed.…”
Section: Introductionmentioning
confidence: 99%